Brazilian Histerini (Coleoptera, Histeridae, Histerinae): a new species, key to the genera, and checklist of species - Leivas, Fernando W. T.; Moura, Daniel P.; Caterino, Michael S. (Zootaxa, 2015)
A new species of the Hister coenosus group from southern Brazil is described. Hister lucia sp. nov. is the largest Hister sp. in the New World, and is also distinguished by its dorsally and laterally concave mandibles. The three genera of Histerini recorded from Brazil are keyed, and a checklist of species of the tribe recorded from Brazil is presented. In total, seventeen described species of Histerini are recorded from Brazil, including fifteen of Hister Linnaeus, one of Atholus C. Thomson, and one of Margarinotus Marseul.